Zinc signals in neutrophil granulocytes are required for the formation of neutrophil extracellular traps. Issue 3 (June 2013) - Hasan, Rafah; Rink, Lothar; Haase, Hajo
Zinc signals, i.e. changes in the free intracellular Zn 2+ concentration, are an integral component of signal transduction in several immune cells. The aim of the present study was to investigate if this is also the case in neutrophil granulocytes. One neutrophil function is NETosis, the release of a matrix composed of DNA, chromatin and granule proteins to capture extracellular bacteria within so-called neutrophil extracellular traps (NET). NETosis can be induced by the protein kinase C (PKC) activator 12-myristate 13-acetate (PMA). PMA treatment led to a zinc signal in neutrophil granulocytes. NETosis was inhibited when the zinc signal was sequestered by the membrane permeable high affinity chelator N, N, N ′, N ′, -tetrakis (2-pyridylmethyl)ethylenediamine (TPEN). PKC-mediated NET formation depends on the production of reactive oxygen species (ROS) by NADPH oxidase. Inhibition of NADPH oxidase with diphenyleneiodonium chloride blocked ROS formation and NETosis, as well as the zinc signal. TPEN, however, had no effect on PKC activity and ROS production, indicating that Zn 2+ is not required for activation of PKC, but for signals downstream of ROS production. In conclusion, zinc signals are an essential component of the ROS-dependent signal transduction leading to NETosis.